The normal and the pathological - DeLisi, Matt (Routledge handbook of homicide studies, 2024)
Drawing on Durkheim’s concept of the normal and the pathological, the current chapter leverages 25 years of consultant, practitioner, and research experiences to inform four professional observations about the normal and pathological features regarding the developmental course, psychopathology, and behavioral features of homicide offenders. These are: (1) In terms of psychopathology, normal is a relativistic term depending on whether the comparison group is non-offenders in the general population, other criminal offenders, or other homicide offenders. (2) Some pathological homicidal features are so routinized that they are commonly construed as normal. They are not. (3) Pathological homicidal ideation is so common, chronic, and salient to the most serious offenders that the impulse and rationalization to murder is normalized. (4) Although a rare event compared to other violent felonies, prior murder predicts subsequent homicide perpetration to a significant degree.